Superfield continuous spin equations of motion - I.L. Buchbinder; S. James Gates, Jr.; K. Koutrolikos (Physics Letters B, 2019)
We propose a description of manifestly supersymmetric continuous spin representations in 4D,N=1 Minkowski superspace at the level of equations of motions. The usual continuous spin wave function is promoted to a chiral or a complex linear superfield which includes both the single-valued (span integer helicities) and the double-valued (span half-integer helicities) representations thus making their connection under supersymmetry manifest. The set of proposed superspace constraints for both superfield generate the expected Wigner's conditions for both representations. Keywords: Supersymmetry, Continuous spin